Dietary niacin intake and mortality among chronic kidney disease patients - Zhou, Zhengxi; Yao, Xiaotian (Frontiers in Nutrition, 2024)
The relationship between niacin and the risk of mortality in chronic kidney disease (CKD) patients remains unclear. This study aims to investigate the potential correlation. Methods This cohort study utilized data from the 2003-2018 National Health and Nutrition Examination Survey (NHANES). The study included 6,110 patients with CKD aged 18 years or older. Weighted Cox proportional hazards models and restricted cubic splines (RCS) were employed to estimate hazard ratios for all-cause mortality and cardiovascular disease (CVD) mortality. Niacin intake was estimated using the 24-hour dietary recall method, based on the type and amount of food consumed. All-cause mortality and cardiac mortality rates were determined using National Death Index (NDI) mortality data (as of 31 December 2018).The median niacin intake was 20.89 mg/day, with an interquartile range of 15.67-27.99 mg/day. During the follow-up period (median of 87 months), there were 1,984 all-cause deaths, including 714 CVD deaths. Compared with low niacin intake, the multivariate-adjusted hazard ratio for dietary intake of 22 mg or higher was 0.71 (95% CI, 0.57-0.88) for all-cause mortality and 0.75 (95% CI, 0.57,0.98) for CVD mortality.Dietary niacin intake is associated with a reduction in all-cause and cardiac mortality among CKD patients.